Mapping in Conflict Regions: Analyzing the Documentation of Historical Sites on OpenStreetMap between Palestinians and Israeli Settlers in the West Bank - Rahaf Hafitha (An-Najah National University, 2025)
The history of the Israeli-Palestinian conflict is long and has extended over decades, during which Israeli settlers have attempted to control the land of Palestine by using various methods and telling different narratives. With the development of technology and the emergence of volunteered geographic information (VGI) platforms such as the OpenStreetMap (OSM) platform, they play an important role in documenting sites in geopolitically contested regions such as the West Bank. This study aims to analyze the contributions of both Israeli and Palestinian settlers on the OpenStreetMap platform and study the motives behind each party's contributions. The research follows a quantitative approach, combining spatial analysis and Metadata analysis to assess the extent and accuracy of coverage of historical sites on OSM and to examine the contributions of Palestinians and Israeli settlers to the platform. Furthermore, a questionnaire was made to measure Palestinian awareness about OSM platform, The questionnaire included 340 respondents from across the West Bank. The results reveal a clear difference between the historical sites documented on OSM (653) and those found in official and academic records (1928). This is due to the voluntary nature of the platform, which allows local residents to document sites from their own perspectives, free from formal legal restrictions. Furthermore, 63.25% of historical sites located in Area C under Israeli control, and 397 sites (≈61%) fell within Israeli areas of influence compared to 266 sites (≈41%) in Palestinian areas. Metadata analysis revealed that Israeli users documented 29 sites and Palestinians 27 from a sample of 115 users, but Israeli contributions were generally more detailed and accurate, while many Palestinian contributions were misclassified or limited.
رسم الخرائط في مناطق الصراع: تحليل توثيق المواقع التاريخية على خرائط الشارع المفتوح بين الفلسطينيين والمستوطنين الإسرائيليين في الضفة الغربية